Perancangan Green Procurement Melalui Integrasi Metode Environmental Management System (EMS) dan Life Cycle Assessment (LCA) pada Pupuk Super Dolomit (Studi Kasus di PT. Polowijo Gosari Gresik) - Andesta, Deny; Futurhesa, Dwi Anggraini (Rekayasa, 2009)
The most important and it's very_ influences in developing and national industry is the usage on natural resources which is not balanced due to the exploitative and egosectoral system. As a super dolomite fertilizers company_, PT. Polowijo Gosari Gresik uses dolomite rock as a raw matenals takenfr_om karst area. In theJact, this raw materials taking will causes karst ecological destruction. Not only the exploration process but also high voltage machines using resulted negative effect. For that reason, thzs research attempt to provide same solving problems  through design improvement to minimalize the impact by using green procurement conc t. The tfesign concept of green procurement is done through the integrated method of Life Cycle Assessment (LCA) and Environmental Management System (EMS). This design ofgreen procurement result the significant decline impact on the value of raw material consumption 8.2x1014 initially become 1.76x1()4 and the decreasing usage ofhigh voltage machines which is  3.93x107 initillly become 3.35x10"8•Keywords: Dolomite, Green procurement, Environmental Management System, LCA